Intracoronary nitrite suppresses the inflammatory response following primary percutaneous coronary intervention. Issue 7 (28th September 2016) - Jones, Daniel A; Khambata, Rayomand S; Andiapen, Mervyn; Rathod, Krishnaraj S; Mathur, Anthony; Ahluwalia, Amrita
Abstract : Objective: Recent work suggests that intracoronary nitrite reduces myocardial infarct size following primary percutaneous coronary intervention (PPCI) for acute myocardial infarction (AMI), although the exact mechanisms are unclear. We explored the effects of nitrite on reperfusion-induced inflammation, by assessing the levels of specific pro-inflammatory mediators, chemokines and adhesion molecules in plasma and circulating cell subtypes as exploratory end points in the NITRITE-AMI cohort. Methods: Peripheral blood leucocyte subsets, cell adhesion molecules, high-sensitivity C reactive protein (hs-CRP), the monocyte and neutrophil chemoattractants CCL2 and CXCL1, CXCL5, respectively were measured in the blood of patients who received either intracoronary sodium nitrite (N=40) or placebo (N=40) during PPCI for AMI. Major adverse cardiac events were recorded at 3 years post-PPCI. Results: In the placebo-treated patients, total circulating neutrophil numbers and levels of hs-CRP were raised postreperfusion and then decreased over time; in nitrite-treated patients these changes were suppressed compared with placebo up to 6 months post-PPCI (p<0.01). This effect was associated with reduced expression of neutrophil CD11b, plasma CXCL1, CXCL5 and CCL2 levels (p<0.05). There were no differences in the number of other any other leucocyte population measured (monocytes and lymphocytes) or activation markers expressed by these cells between the treatment groups. These effects were associated with a reduction in both microvascular obstruction and infarct size. Conclusions: Important reductions in neutrophil numbers and activation post-PPCI in patients with ST elevated myocardial infarction were associated with nitrite treatment, an effect we propose likely underlies, at least in part, the beneficial effects of nitrite upon infarct size. Trial registration number: NCT01584453 .